Evaluasi Peggunaan Aplikasi Peduli Lindungi Pada Kalangan Masyarakat Umum Menggunakan Metode Pieces - Ramadani, Indha Suci; Utama Jaya, Joy Nashar (Journal of Applied Informatics and Computing, 2022)
COVID-19 Pandemic makes all Government in the world making somekind of some safety measures into increasing the health safety of it citizen. Efforts have been made to reduce the spread. Indonesian government came up with the "PeduliLindungi" application to protect people in their daily life. This study seeks to determine the level of satisfaction of "PeduliLindung" users using PIECES methode. This type of research is based on primary data which is directly given to respondents using a questionnaire. The main respondents are users who have used (PeduliLindungi). The respondent's questionnaire reached 69 samples and used the Slovin formula with an error tolerance of 5% so that only 59 samples were taken. These results show that efficiency has a significant effect on application users with P-Values "‹"‹< 0.05 and T-Statistics > 1.99 while the other five are still not significant because P-Values "‹"‹> 0.05 and T-Statistics < 1.99. The final number of T-Statistics in Efficiency domain is 4.740 which is bigger >1.99 which means that "PeduliLindungi" Application is efficient into helping the public or government tracking and reducing the COVID-19 Pandemic in spreading much further.